1988
DOI: 10.1128/aem.54.5.1216-1221.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stirring and Hydrogen on Fermentation Products of Clostridium thermocellum

Abstract: Clostridium thermocellum produces ethanol, acetate, H2, and CO2 as major fermentation products from cellulose and cellobiose. The performance of three strains of this microorganism was studied to assess the potential use in producing ethanol directly from cellulosic fiber. Depending on the bacterial strain, an ethanol/acetate product ratio from 1 to as high as 3 was observed in unstirred cultures. Vigorous stirring during growth resulted in a threefold decrease in the ethanol/acetate ratio. The H2 content in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(42 citation statements)
references
References 21 publications
2
36
0
4
Order By: Relevance
“…proteoclasticus produces acetate, ethanol, propionate, formate, butyrate and hydrogen (Tarlera et al 1997). In addition, Clostridium thermocellum, which is known to produce ethanol, was also detected (OTU-18) (Lamed et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…proteoclasticus produces acetate, ethanol, propionate, formate, butyrate and hydrogen (Tarlera et al 1997). In addition, Clostridium thermocellum, which is known to produce ethanol, was also detected (OTU-18) (Lamed et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…NADH-dependent H2 synthesis at reported cellular NADH/NAD + ratios is unlikely to be utilizable in a biotechnological process if the reaction reaches equilibrium at the very low partial pressure of H2 (60 Pa) that has been theoretically predicted (Angenent et al, 2004). Furthermore, it has been reported that the solubility of H2 in microbial cultures can exceed the theoretical limit derived from Henry's Law by up to 80 times (Lamed et al, 1988;Pauss et al, 1990), potentially lowering the theoretical partial H2 pressure limit for H2 synthesis substantially further. In contrast, there are several convincing reports (Lamed et al, 1988;Kumar et al, 2001) suggesting that GAP-dependent H2 synthesis indeed is operational in several microorganisms, even at partial H2 pressure levels substantially above the limit suggested by Angenent and colleagues (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that the solubility of H2 in microbial cultures can exceed the theoretical limit derived from Henry's Law by up to 80 times (Lamed et al, 1988;Pauss et al, 1990), potentially lowering the theoretical partial H2 pressure limit for H2 synthesis substantially further. In contrast, there are several convincing reports (Lamed et al, 1988;Kumar et al, 2001) suggesting that GAP-dependent H2 synthesis indeed is operational in several microorganisms, even at partial H2 pressure levels substantially above the limit suggested by Angenent and colleagues (2004). For example, based on fermentation balance analysis of mutant strains in which NADH-consuming reactions had been deleted, it was deduced that Enterobacter aerogenes most likely does catalyse NADH-dependent H2 synthesis (Nakashimada et al, 2002) even under closed batch conditions.…”
Section: Introductionmentioning
confidence: 99%
“…刘如林等人 [10] 指出当分子氢 浓度超过 60%时, 固氮酶能力会受到抑制; 同时二氧 化碳的浓度也影响氢气的合成速率以及最后的产氢 得率 [11] , 有效地去除反应体系中的二氧化碳, 可以 减少与 NADH 的竞争, 从而增加氢气的合成. 向液相喷射气体是减小液相中氢气和二氧化碳 分压力的一种有效方法 [9,12] , 同时还可以增强反应液 的混合以提升反应器的整体性能 [13] . 在厌氧发酵菌 纯培养过程中, 向液相中鼓入气体(Ar, H 2 , N 2 )可以 改变代谢产物的相对比例 [14,15] , 同时提高产氢得率.…”
unclassified